1995
DOI: 10.1002/jobm.3620350309
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acetic acid on xylose fermentation to xylitol by Candida guilliermondii

Abstract: The effect of acetic acid concentration on xylose-fermentation to xylitol by Candida guilliermondii FTI 20037 was evaluated in semisynthetic medium containing different concentrations of the acid. Increasing acetic acid concentration up to 1.0 g/l favored xylitol yield and productivity, with maximum values of 0.82 g/g and 0.57 g/l.h, respectively. The presence of acetic acid reduced cell production at all concentration. Furthermore, acetic acid was assimilated by the yeast together with the sugars and was depl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
52
0
28

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(88 citation statements)
references
References 22 publications
(24 reference statements)
8
52
0
28
Order By: Relevance
“…The arabinose assimilation pathway of yeast is very similar to that of xylose, however, as observed in this study, arabinose consumption is much slower than that of xylose. Similar behavior was observed by Lima (2004) during fermentation of sugar cane bagasse hemicellulosic hydrolysate with C. guilliermondii, as well as synthetic medium by Felipe et al (1995).…”
supporting
confidence: 77%
“…The arabinose assimilation pathway of yeast is very similar to that of xylose, however, as observed in this study, arabinose consumption is much slower than that of xylose. Similar behavior was observed by Lima (2004) during fermentation of sugar cane bagasse hemicellulosic hydrolysate with C. guilliermondii, as well as synthetic medium by Felipe et al (1995).…”
supporting
confidence: 77%
“…Acetic acid interference results in an increase in the ATP required for this maintenance function, as well as interferes with the cell morphology. Lawford and Rousseau (8) reported that acetic acid toxicity is related to the ability of undissociated (protonated) A previous study on the bioconversion of xylose to xylitol employing C. guilliermondii FTI 20037 cultivated in semisynthetic medium revealed that the acetic acid concentration determines its degree of toxicity, since a concentration as low as 1.0g/L favoured the bioconversion, while concentrations higher than 3.0g/L inhibited xylose consumption and xylitol formation (4).…”
Section: Introductionmentioning
confidence: 99%
“…Tempo inicial Tempo final (72 h ácido acético e fenólicos sobre as leveduras (FELIPE et al, 1995;LOHMEIER-VOGEL, 1998;FELIPE, 2004;LIMA et al, 2004;SILVA et al, 2004;JONSSON et al, 2013). Particularmente com relação ao efeito destes tóxicos e mesmo do hidrolisado hemicelulósico sobre leveduras da Antártica não há relatos na literatura.…”
Section: Levedurasunclassified